THE MANAGEMENT OF GREEN OPEN SPACE IN REGENCY INDRAGIRI HULU (CASE STUDY OF PEMATANG REBAVILLLAGE) - Surya Ernita; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Green Open Space (RTH) Embankment Reba, Indragiri Hulu District was actually built by the Government for recreation, relaxing, playing and exercising.To manage the necessary Green Open Space (RTH), policies are needed. This research describes policy implementation of Green Open Space (RTH) management policies in Indragiri Hulu Regency which is based on the Regulation of the Minister Of Home Affairs Number. 1 Of 2007 concerning Green Open Spaces (RTH) Management, further supported by Regent's Regulation Number 52 of 2016 concerning Position, Organizational Structure, Duties and Functions as well as Work Procedures of the Public Works and Spatial Planning Office of Indragiri Hulu Regency. The theory used in this research is Terry’s (2013) Management theory which includes 4 (four) stages, namely planning, organizing, implementing and monitoring. The research method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. Selection of research informants using snowball sampling technique. The result of this study indicate that the  inhibiting factors in the Governance of Green Open Spaces (RTH) in Indragiri Hulu Regency, especially Pematang Reba Village are the large number of facilities that cannot be functioned and the lack of improvements to existing facilities and infrastructure, the absence of Regional Regulation (Perda), low awareness society and the limited budget provided.  Keywords : Management, Policy